Pengaruh Work-Life Balance Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Sumber Makmur Di Jambe Kabupaten Tangerang - Khoiru Maksum; Ali Zaenal Abidin (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract The main objective of this study is to determine the effect of Work-life Balance and job satisfaction on employee performance, both partially and simultaneously. This study uses a quantitative method. Data collection techniques are carried out through observation, documentation, and distribution of questionnaires to the entire population of 60 employees using saturated sampling techniques. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, and determination coefficients with the help of SPSS. The results of the study indicate that Work-life Balance has a significant effect on employee performance with a determination result of 38.7% and the hypothesis test obtained t count> t table or (6.046> 2.001). Job satisfaction has a significant effect on employee performance with a determination result of 70,8% and the hypothesis test t count> t table or (11.851> 2.001). Work-life Balance and job satisfaction simultaneously have a significant effect on employee performance with a regression equation Y = 2.329 + 0.026 X1 + 0.985 X2. The coefficient of determination value is 70.8% while the remaining 29.2% is influenced by other factors outside this study. The hypothesis test obtained a calculated f value > f table (69.075 > 3.16). The conclusion of this study shows that the balance between work and personal life, as well as a high level of job satisfaction, can increase employee overall performance. This study provides implications for management to strengthen work balance policies and employee satisfaction improvement programs, and for further research it is recommended to add other variables such as work motivation, work environment, and organizational commitment to broaden understanding of the factors that influence employee performance